Practices of financial income accounting in budget organizations - N. Abdullayeva (Research Parks Publishing LLC, 2021)
This article describes the fixed assets recognition in budget organizations and their practical aspects. There are practical recommendations for the recognition and accounting of fixed assets in budget organizations